Pengaruh Kemasan dan Susunan terhadap Sifat Fisik Buah Mangga Golek selama Transportasi - Amanto, Bambang Sigit (Caraka Tani: Journal of Sustainable Agriculture, 2004)
Packaging has been designed for degrade of vibration and presser that to create broken and injury during transportation. The broken and injury fruit impact respiration process and to be continued. Mango fruit that injury impact respiration process. The aims of research was to study of physic characteristic of mango fruit “golek’’ to kind of packaging and setting in the packaging during transportation. The result of research was (1) There isn’t really impact to very really impact at the treatment of the fruit sstting to change colour, hardness and removal weight in packaging during transportation, (2) There isn’t really impact to very really impact at the treatment of kind of packaging to change colour and removal weight during transportation, (3) Packaging that been made from bamboo (basket) giving a the best of value was compared the others packaging to hardness of mango fruit during transportation.